(untitled) (Filologia e Linguística Portuguesa, 2004)
Aiming at contributing to the collection of reliable concrete data about the issue oflinguistic borrowings in the constitution of the lexicon of the Portuguese language, this paper comments upon standpoints of authors who reflect on this collection focusing on neologism and archaism, borrowings being included in the latter. With brief references to authors from other times, the follwoing works are highlighted：Grammatica da lingoagem portuguesa (Grammar o f the Portuguese language), by Fernão de Oliveira (1536), the pedagogical work by João de Barros (1540), and Dialogo em defensão da lingua Portuguesa (dialog in defense o f the Portuguese language), by Pero de Magalhães de Gândavo (1574). All the three authors are legitimate representatives, in portugal, of the thoughts about that issue in the historical period considered, the first two authors were the first grammarians of the language